Effect of micro sprinkler irrigation intervals on onion (Allium cepa L.) production compared to surface irrigation under Kassala conditions, Sudan - Khalifa, Ahmed; Hamed, Ibtihal; Algali, Mohamed; Ahmed, Shaker; Ali, Ali; Babiker, Ebtehag; Ali, Mohamed; Heng, Lee (Gezira Journal of Agricultural Science; Vol 16 No 2 (2018), 2018)
An experiment was conducted to evaluate the effects of surface and micro sprinkler irrigation intervals on onion production under Kassala conditions. Three irrigation intervals were applied under micro sprinkler irrigation; every day, three days and at five days compared to farmers practice, (surface irrigation every 7 days). The treatments were replicated four times in a randomized complete block design. The results showed that higher yields were produced under micro sprinkler irrigation than surface irrigation. Moreover, micro sprinkler every day recorded the highest yield in both seasons. Therefore, micro sprinkler irrigation system was saving water by about 119% and 101% for seasons one and two, respectively, as compared to surface irrigation. The highest values of water productivity and economic water productivity were obtained under micro sprinkler irrigation system every day as compared to surface irrigation. Irrigation every day under micro- sprinkler irrigation was the most economic and had higher net benefit compared to surface irrigation.      اجريت التجربة لتقييم أداء الري السطحي و فترات الري بالرش الدقيق لإنتاج البصل تحت ظروف كسلا. تم تطبيق ثلاث فترات ري تحت الري بالرش الدقيق على النحو التالي: كل يوم وثلاثة أيام وخمسة أيام مقارنة بممارسات المزارعين (الري السطحي) كل 7 أيام. تم تكرار المعاملات أربع مرات في تصميم القطاعات العشوائية الكاملة. أظهرت النتائج أن أعلى انتاجية كانت تحت الري بالرش الدقيق مقارنة مع الري السطحي. وعلاوة على ذلك، سجل الري بالرش الدقيق كل يوم أعلى انتاجية في الموسمين. نظام الري بالرش الدقيق وفر مياه الري بنسبة 119٪ و 101٪ للموسم الأول والثاني، على التوالي مقارنة بالري السطحي. وقد تم الحصول علی أعلی قیمة لإنتاجية المیاه وإنتاجیة المیاه الاقتصادیة تحت نظام الري بالرش الدقيق کل یوم مقارنة بالري السطحي. الري يوميا تحت الري بالرش الدقيق هو الأكثر اقتصادا وله صافي فائدة أعلى مقارنة بالري السطحي.